Analisis Pengaruh Dana Otonomi Khusus dan Pendapatan Asli Daerah terhadap Produk Domestik Regional Bruto pada Kabupaten dan Kota di Provinsi Papua Barat - Rengga Bayu Widiprana (Fakultas Ekonomi dan Bisnis, Universitas Papua, 2022)
This study aims to analyze the effect of Dana Otonomi Khusus and Pendapatan Asli Daerah (PAD) on Produk Domestik Regional Bruto (PDRB) in Regencies and Cities in West Papua Province, during period 2018 to 2021. This study uses quantitative research methods with analysis panel data regression using the double logarithm function. The application used to process the data is the STATA application. The results showed that the Dana Otonomi Khusus had an insignificant relationship to PDRB, while PAD had a positive and significant relationship to PDRB. The results of the study also show that the Dana Otonomi Khusus and PAD together have a significant influence on PDRB in Regencies and Cities in West Papua Province.